Hubungan mekanisme koping dengan tingkat kecemasan pasien kanker yang menjalani kemoterapi - Aryati Andinata; Erna Marni; Susi Erianti (Jurnal Cakrawala Promkes, 2020)
Chemotherapy refers to a procedure treatment by using drugs that can kill cancer cells. The chemotherapy can cause anxiety of patient because they feel frightened physically and mentally. Therefore, the proper coping mechanism should be done to face this problem. This research aims to know about the correlation between coping mechanism and the anxiety level of the patient with cancer who was doing chemotherapy at RSUD Arifin Achmad Riau Province. This is quantitative research with descriptive correlation design and cross-sectional approach. The instrument used in this research is questionnaire. There is 96 respondent involved as the sample for this research. All of the respondents is the patient with cancer who was doing chemotherapy at RSUD Arifin Achmad Riau Province. The author used an accidental sampling method. The analysis style used in this research is the single variable with frequency distribution and two variable with the Kolmogorov-Smirnov statistic test. The result of this research shows that there is no significant effect of coping mechanism towards the anxiety level with p-value = 1,00 (p â‰¥ 0,05). The author gives a suggestion to RSUD Arifin Achmad Riau Province to increase the quality of coping mechanism to their patient.